The conceptual framework: establishing health literacy module for indigenous people in Malaysia - Alias, Normalina; Jaafar, Mohamad Helmy; Mat Yusof, Afzan; Md Isa, Muhammad Lokman (Faculty of Medicine, University of Malaya, 2019)
This paper proposed a conceptual model on developing a new Health Literacy Module for Indigenous People in Malaysia. This proposed model could be used as a reference for researchers to develop new strategies to overcome health issues on Indigenous People. The proposed model incorporated three (3) phases which are (i) Phase 1: To determine the Knowledge, Attitude & Practice (KAP) on parasitic infections among Indigenous People, (ii) Phase 2: To develop self-useful kit for Indigenous People according to the needs in Phase 1, (iii) Phase 3: To develop a health literacy module of parasitic infections as a referral for Indigenous People. This research will have a significant contribution to provide an in-depth knowledge on identification of health care problems related to parasitic infections towards the development of health literacy module for Indigenous People. Authors will propose new or adapted or/and adopted tools/products/guidelines to be established based on the findings of this research. The findings are aimed to improve quality of life for Indigenous People in Malaysia.